Management of finances in the implementation of infrastructure development programmes in the Limpopo Provincial Government - Semenya, Portia Annah (My University, 2018)
The provision of infrastructure delivery programmes in Limpopo province is an important agent in the reduction of poverty, unemployment and strengthening of social capital. The infrastructure development programmes create opportunities for job creation through approaches such as maintenance of existing infrastructure in order to retain resources in the local areas. However, the provision of basic infrastructure still faces serious challenges, notwithstanding the fact that the PFMA and Treasury Regulations (issued by the National Treasury in terms of Section 76 of the PFMA) provide for control measures government has put in place for effective and efficient service delivery in general. The objective of this study was to scrutinise management of finances in the planning, implementation and monitoring of infrastructure programmes and further seek to propose measures to strengthen financial management controls in the implementation of infrastructure programmes to bolster service delivery in the Limpopo province. The literature reviewed indicated that successful implementation of infrastructure development in the province depends on skills and knowledge of the players and financial resources. This study used qualitative research methodology in examining the management of finances in the planning, implementation and monitoring of infrastructure programmes in the Limpopo provincial government. An open-ended questionnaire was used to collect data from the participants. The researcher utilised purposive selection method to obtain information from relevant participants who are directly involved in infrastructure management. The study revealed that Limpopo government departments do not utilise capital budgeting models to appropriately plan and fund infrastructure projects. There are challenges, including procurement processes, lack of appropriate skills to monitor and implement infrastructure projects and lack of standard operating procedures to encourage a culture of uniformity, responsibility and accountability in the processing of payments.
M.Tech (Department of Accountancy, Faculty of Management Sciences), Vaal University of Technology.
Keywords: social capital, procurement processes, standard operating procedures; infrastructure programmes; Infrastructure (Economics) -- South Africa -- Limpopo.; Finance -- Management -- South Africa -- Limpopo.